Analysis of p-y curves of sand and clay using PLAXIS 3D - Chew, Andrew Ying Cheng (2019)
In this study, PLAXIS 3D is used to simulate the lateral translation of a long and rigid pile in sands and clays. In this paper, the p-y curves are obtained from the shear profile of the laterally translated pile, and are then normalised such that its horizontal and vertical axis are dimensionless. The effects of fundamental soil properties such as undrained shear strength of the clays, friction angle of the sands and their respective stiffness parameters on the p-y curves are investigated. The p-y curves are compared to recommended p-y curves by Det Norske Veritas (DNV) and the American Petroleum Institute (API). The total displacement vectors of soil movements based on screen captures of PLAXIS 3D are discussed to support the results from the analysis of p-y curves. Finally, the sand and clay models are validated with field testing of laterally loaded piles. Major findings of this paper are that: (1) p-y curves can be successfully extracted by using the shear profile of the laterally loaded pile, (2) the soil behaviour around the laterally translated pile is complex especially near the ground surface, up to a depth of 3 D for clays and 2.5 D for sands.